Trailing Nocardiosis- A Non-healing Wound Infection: Where does Bangladesh stand? An Updated Review! (The Journal of Ad-din Women's Medical College, 2023)
Abstract not availableThe Journal of Ad-din Women's Medical College; Vol. 10 (1), Jan 2022; p 42-47